Innovation and protection of accounting software: a comparative study between Brazil and Latin America - Dias, Leonôra Virginia de Jesus; Parisi, Baby de Fátima Barbosa; Santos, José Wendel dos (Brazilian Journal of Production Engineering, 2024)
This study aimed to identify trends in accounting activities in Brazil and their positioning in Latin America. With an applied nature, mixed and exploratory approach, the search for data was carried out between June and October 2022 on the INPI portal and the LATIPAT database, with 31 and 37 records being retrieved, respectively. After the analyses, it was concluded that in Brazil there is an average of 5 registration requests per year; almost 84% are held by legal entities; the registrations are concentrated in the fields of administration, economics, industry, information, and finance; and the predominant programming languages are Java, Delphi, HTML and SQL. As for Latin America, the requests considered patents, a total of 37 applications were found, distributed between Spain and Peru. The main contribution of this research lies in identifying trends and gaps that can guide strategic decision-making, with direct implications for the practice and development of innovative software.
Keywords: Software registration; Accounting; Intangible assets; Computer programs